Methodology of students' professionally-applied physical training in universities - Pylypey L.P (Kharkov National Pedagogical University, 2012)
Real system of physical education that exists in Ukraine is considered; the ineffectiveness of physical training of students for future life and production activities is shown. In modern conditions the structure of physiological requirements and working conditions is changing and, accordingly, there are additional requirements for professionally-applied physical training. The model of the educational process for credit-module system in high school is given. Theoretical and methodological reasoning of professionally-applied physical training methodology in university of economic profile is carried out. Management options for physical training of students are proposed. The systems of computer technology of professionally-applied physical training are considered.